FACTORS AFFECTING DIVIDEND PAYOUT: EMPIRICAL INVESTIGATION FROM CEMENT SECTOR OF PAKISTAN - Ахмад, Н.; Ансари, М.; Шамси A. (Journal of Economic Research & Business Administration, 2019)
Dividend policy/payout (DP) is one the areas of finance where extensive research has been conducted to find out the determinants that why firms pay the dividend and what motivates them to share their earnings with shareholders. This situation is termed as a puzzle by researchers. To solve this puzzle, researchers have outlined various financial and non-financial factors. This research is carried out to find the effect of financial factors viz. size, profitability, risk, leverage, and liquidity over the DP of the firms listed on Pakistan Stock Exchange (PSX) in the cement sector. Firms involved in the manufacturing of cement are selected and other firms of the sector are excluded. Data for ten years i.e. from 2009 to 2018 has been extracted from the published annual financial statements of the firms. To verify the relationship between dependent and independent variables, the bivariate correlation has been applied and to find the best-fit regression model, backward multiple regression has been applied. According to the findings from backward multiple regression, profitability and liquidity are the factors that influence the dividend payouts of the firm positively and significantly. Whereas, size, risk, and leverage have failed to show their significance over the dividend payment of the sector.